Hamstrings and quadriceps muscle size and strength in female and male elite competitive alpine skiers - Fitze, Daniel P.; Franchi, Martino V.; Müller Brusco, Clarissa; Engeler, Nadine; Frey, Walter O.; Spörri, Jörg (Frontiers in Physiology, 2025)
Competitive alpine skiing requires a high level of physical fitness to perform sport-specific manoeuvres and to minimise the risk of injury. The aim of this study was to establish reference values for the maximal anatomical cross-sectional area (ACSAmax) of the individual hamstrings (HAM) and quadriceps (QUAD) muscles as well as for the maximal voluntary torque (MVT) during knee flexion (KF) and knee extension (KE) of female and male elite competitive alpine skiers. Ultrasound and dynamometer data were obtained from a largely overlapping but not identical dataset. The ultrasound data were collected from 33 elite alpine skiers (20 women and 13 men), and the dynamometer data were collected from 35 elite alpine skiers (20 women and 15 men). Compared with female skiers, male skiers presented a significantly greater ACSAmax in the biceps femoris short head (BFsh), biceps femoris long head (BFlh), and semitendinosus (ST) muscles, as well as in the entire HAM muscle group. The ACSAmax of the semimembranosus (SM) did not differ significantly between the two sexes. Compared with female skiers, male skiers presented significantly greater ACSAmax values in the vastus lateralis (VL), rectus femoris (RF), vastus medialis (VM) and entire QUAD muscle groups. At VI, there was no significant difference in the ACSAmax between the two sexes. Compared with male skiers, female skiers had a significantly greater proportional SM ACSAmax. In terms of MVT, male skiers presented greater absolute and relative values than females did. There were no differences in the MVT/ACSAmax between the sexes. Neither the HAM/QUAD ACSAmax ratio nor the KF/KE MVT ratio differed between the sexes. The present study provides normative values for the muscle size and strength of the HAM and QUAD muscles of elite competitive alpine skiers. These values can be used as benchmarks for youth alpine skiers striving for the elite level. An interesting finding of the present study was that female skiers had a greater proportional ACSAmax of the SM, as this may be relevant in anterior cruciate ligament injury prevention given the function of tibia internal rotation.